Humanistic aspects of Carolingian Court Poetry: Poetical Technique and Use of Sources in Paul the Deacon's Carmen X - Conti, Marco (Saeculum Christianum. Pismo Historyczne, 2021)
The object of this article is the analysis of a typical specimen of Carolingian court poetry, namely Paul the Deacon's Carmen X, which was written at the very beginning of the so-called Carolingian Renaissance in 781. In my opinion, Paul's poem demonstrates once more how, on the one hand, the poetical technique and use of classical sources and, on the other hand, the crucial influence of the environment of Charlemagne's court that both makes Carolingian poetry an extremely innovative literary form, and strongly connects it with the later phenomenon of Humanism.